Work Values of Public, Nonprofit, and Business Employees: A Cross-Cultural Evidence. Issue 3 (23rd February 2016) - Jaskyte, Kristina
ABSTRACT: Employees' work values, or beliefs about desirability of certain work attributes and outcomes, are believed to drive their motivation to work and stay in certain settings. This article compares work values of business, government, and nonprofit employees in a sample of nations with different cultural orientations—Germany, India, South Korea, Russia, South Africa, and the US. Results showed significant relationship between a country and work values variables, suggesting that a country's culture may have a potential to influence what individuals value in work. Additionally, employees of government, business, and nonprofit sectors differed in their work values in all six countries.